IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE FIFTH-GRADE STUDENTS’ COLLABORATION SKILLS IN SCIENCE LEARNING - RAHMAT SYAHRUDDIN (CV Grasta Glory, 2026)
This study aims to improve fifth-grade students’ collaboration skills in science learning through the implementation of the Project Based Learning (PjBL) model. This research employed Classroom Action Research (CAR) consisting of one cycle that included planning, action, observation, and reflection stages. The participants were 16 fifth-grade elementary school students. Data were collected using observation sheets, interviews, documentation, and pre-test and post-test instruments. The results show a significant improvement in students’ collaboration skills, as indicated by an increase in the average score from 67.8% in the pre-test to 79.3% in the post-test. In addition, mastery learning improved from 25% to 87%. The improvement was evident in students’ ability to communicate effectively, share responsibilities, and actively participate in group work during project implementation. These findings indicate that Project Based Learning is effective in fostering collaboration skills in elementary science learning. Future research is recommended to conduct the study using more action cycles, involve a larger number of participants, and compare PjBL with other instructional models to obtain more comprehensive insights into the development of students’ collaboration skills.